Drought stress in rice: morpho-physiological and molecular responses and marker-assisted breeding - Hassan, Muhammad A.; Dahu, Ni; Hongning, Tong; Qian, Zhu; Yueming, Yi; Yiru, Li; Shimei, Wang (Frontiers in Plant Science, 2023)
Rice (Oryza Sativa L.) is an essential constituent of the global food chain. Drought stress significantly diminished its productivity and threatened global food security. This review concisely discussed how drought stress negatively influenced the rice's optimal growth cycle and altered its morpho-physiological, biochemical, and molecular responses. To withstand adverse drought conditions, plants activate their inherent drought resistance mechanism (escape, avoidance, tolerance, and recovery). Drought acclimation response is characterized by many notable responses, including redox homeostasis, osmotic modifications, balanced water relations, and restored metabolic activity. Drought tolerance is a complicated phenomenon, and conventional breeding strategies have only shown limited success. The application of molecular markers is a pragmatic technique to accelerate the ongoing breeding process, known as marker-assisted breeding. This review study compiled information about quantitative trait loci (QTLs) and genes associated with agronomic yield-related traits (grain size, grain yield, harvest index, etc.) under drought stress. It emphasized the significance of modern breeding techniques and marker-assisted selection (MAS) tools for introgressing the known QTLs/genes into elite rice lines to develop drought-tolerant rice varieties. Hence, this study will provide a solid foundation for understanding the complex phenomenon of drought stress and its utilization in future crop development programs. Though modern genetic markers are expensive, future crop development programs combined with conventional and MAS tools will help the breeders produce high-yielding and drought-tolerant rice varieties.